Knockdown of NDUFC1 inhibits cell proliferation, migration, and invasion of hepatocellular carcinoma - Han, Fang; Liu, Junwei; Chu, Hongwu; Cao, Dan; Wu, Jia; Fu, Hong; Guo, Anyang; Chen, Weiqin; Xu, Yingping; Cheng, Xiangdong; Zhang, Yuhua (Frontiers in Oncology, 2022)
Background: NADH: ubiquinone oxidoreductase subunit C1(NDUFC1) encodes a subunit of the complex I, which may support the structural stability of complex I and assist in its biogenesis. The expression and functional roles of NDUFC1 in hepatocellular carcinoma (HCC) remain unknown. Result: We knocked down the expression of NDUFC1 in HCC cell lines to explore the effects of NDUFC1 down-regulation on HCC in vitro. MTT assay determined that down-regulation of NDUFC1 significantly inhibited cell proliferation. Flow cytometry with (propidium iodide) PI staining indicated silencing of NDUFC1 arrested cell cycle of BEL-7404 cells at G2 phase and SK-HEP-1 cells at S/G2 phase. Annexin V-PI double staining and flow cytometric analysis showed that down-regulation of NDUFC1 significantly increased the population of apoptotic cells. Wound-healing assay and transwell assay indicated that down-regulation of NDUFC1 suppressed the migration and invasion of HCC cells. According to the detection of complex1 activity, we found that the activity of NDUFC1 silenced group decreased, while the content of ROS increased. Furthermore, combined with bioinformatics analysis of senescence-related genes, we found that the silence of NDUFC1 in HCC could induce senescence and inhibit autophagy. In addition, NDUFC1 could correlate positively with cancer-related pathways, among which the p53 pathways and the PI3K/Akt/mTOR pathways.Finally, NDUFC1 is high expression in HCC specimens. High NDUFC1 expression was associated with poor prognosis and was an independent risk factor for reduced overall survival (OS). Conclusion: Our study indicated for the first time that NDUFC1 is an independent risk factor for the poor prognosis of HCC patients. NDUFC1 may promote tumor progression by inhibiting mitochondrial complex I and upregulating ROS through multiple cancer-related and senescence-related pathways of HCC, including p53 pathways and PI3K/Akt/mTOR pathways. We suppose that NDUFC1 might be a potential target for the mitochondrial metabolism therapy of HCC.